Plan de Negocios para la creación de un centro de capacitación en habilidades técnicas para mujeres de la zona rural del cantón Latacunga. - Gutiérrez Reinoso, Andrea Elizabeth (2023)
The present work entitled Business Plan for the creation of a training center in technical skills for women in the rural area of ​​the Latacunga Canton had the objectives of developing a market study that identifies the unsatisfied demand for training in technical skills for women in the area. of the Latacunga Canton, proposes a technical and administrative study on the size, location and organizational structure of the training center and carries out a study and financial evaluation that determines the economic viability of the training center. The methodology used was based on the use of a descriptive quantitative approach considering a population of 57,967 women with a sample of 377 to whom a questionnaire was applied. The results found describe the feasibility of executing this business plan with an initial investment of $54,318.80 USD, real net value of $8,410.03 USD, IRR of 20.85%, recovery period of 2 years 8 months, and benefit cost of $1.33 USD.